Diabeł uczłowieczony - wersje współczesne - Błażejewski, Tadeusz (Acta Universitatis Lodziensis. Folia Litteraria Polonica, 2001)
The author presents the problem of humanizing the demon and giving to the human being the demonic features. The analysis focuses on modern Polish prose, especially on such works: Cz. Miłosz, A. Szczypiorski, J. Broszkiewicz, A. Gołubiew, T. Konwicki, G. Herling- Grudziński. He is mostly interested in the devil figure as an evil spirit.